2007
DOI: 10.1038/sj.bjp.0707146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural and novel synthetic jasmonates in experimental metastatic melanoma

Abstract: Background and purpose: No current treatment reliably affects the course of metastatic melanoma. Consequently, novel approaches to the control of metastasis are actively sought. The overall goal of the present study was to identify new antimetastatic agents active against melanoma cells. Experimental approach: Two directions were taken: 1. To determine whether the natural plant hormone methyl jasmonate, which kills cancer cells selectively, can suppress the characteristic metastatic behavior of B16-F10 melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…In the leukemic cell line, Molt-4, the cytotoxicity of methyl jasmonate (MJ) was shown to be transcription-and translation-independent (Flescher, 2005). In addition, the jasmonates are effective against drug-resistant cells Flescher, 2005;Reischer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the leukemic cell line, Molt-4, the cytotoxicity of methyl jasmonate (MJ) was shown to be transcription-and translation-independent (Flescher, 2005). In addition, the jasmonates are effective against drug-resistant cells Flescher, 2005;Reischer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it is reported the synthesis of numerous and varied series of derivatives of MeJA, predominantly halogenated (-Cl,-Br, -F) structures, which similar to JA and its derivatives, they exhibit interesting and in some cases potent anti-neoplastic properties (Ishii et al 2004;Reischer et al 2007;Park et al 2010;Zhao et al 2010), but it is noteworthy that in each of the proposed series does not have reported the production of derivatives with keto group reduced and the potential inhibition of cell growth observed with these series of compounds does not exceed the IC50 obtained with the derivatives reported here. Qian et al 2004 reported that synthetic hydroxyl-containing jasmonates may induce different levels of plant defense responses, which are associated with different levels of enhanced metabolic activity for secondary metabolite biosynthesis.…”
Section: Study On Tumor Cell Linesmentioning
confidence: 99%
“…Jasmonate presented selective cytotoxicity in cancer cells in patients with chronic lymphocytic leukemia, leaving the nontransformed cells intact. 19,20 These compounds are poorly water-soluble, and cannot be administered intravenously or adequately absorbed by the body. However, for MJ, there are no studies on delivery systems that could circumvent these problems.…”
Section: Silva Et Almentioning
confidence: 99%